Evaluation of the distribution of cyanide in the peels, pulps and leaves of three new yellow cassava (Manihot esculenta Crantz) varieties for potential livestock feeds - Udeme, Nelson; Okafor, Polycarp; Eleazu, Chinedum (Progress in Nutrition, 2017)
The total and free cyanide levels in fresh peels, pulps and leaves of three cassava (Manihot esculenta Crantz) varieties: TMS 01/1368 (UMUCASS 36), TMS 01/1412 (UMUCASS 37) and TMS 01/1371 (UMUCASS 38) were determined using standard enzymatic methods. Results showed that the total cyanide levels in the peels, pulps and leaves of these cassava varieties were lower than the reference range for fresh cassava peels, pulps and leaves which were given as 364.2 to 814.70 for the peels, 34.3 to 301.30 for the pulps and 200 to 800 mgkg-1 CN- for the leaves respectively. The cyanide levels in the peels, pulps and leaves of TMS 01/1412 were found to be lower than that of TMS 01/1368, TMS 01/1371 and the reference range. Furthermore, the peels had the highest levels of total and free cyanide followed by the leaves and lastly the pulp. Results obtained from this study indicate the usefulness of the peels, pulps and leaves of these cassava varieties as potential livestock feeds. Finally, results obtained suggest that these cassava byproducts may require simpler processing compared with byproducts of high cyanide cassava varieties before being converted into livestock feeds.